Leadership Manipulation and Ethics in Storytelling - Auvinen, Tommi P.; Lämsä, Anna-Maija; Sintonen, Teppo; Takala, Tuomo (2013)
This article focuses on exerting influence in leadership, namely manipulation in storytelling. Manipulation is usually considered an unethical approach to leadership. We will argue that manipulation is a more complex phenomenon than just an unethical way of acting in leadership. We will demonstrate through an empirical qualitative study that there are various types of manipulation through storytelling. This article makes a contribution to the literature on manipulation through leadership storytelling, offering a more systematic empirical analysis and a more nuanced view of the topic than previously existed by outlining how managers engage in manipulative storytelling and what kind of ethics they link to their manipulation in leadership. Four types of manipulation in storytelling are identified in the study: humorous, pseudo-participative, seductive and pseudo-empathetic. From an ethical perspective, we will show that manipulation is not always self-evidently reprehensible. We will conclude that the dominant ethical justification for manipulation stems from its consequences.
Keywords: Social Constructionism; Narration; Narrative; Storytelling; Manipulation; Unethical; Ethics; Leadership